XRCC1 phosphorylation by CK2 is required for its stability and efficient DNA repair. - Parsons, J; Dianova, I; Finch, D; Tait, P; Ström, C; Helleday, T; Dianov, G (2010)
XRCC1 is a scaffold protein that interacts with several DNA repair proteins and plays a critical role in DNA base excision repair (BER). XRCC1 protein is in a tight complex with DNA ligase IIIalpha (Lig III) and this complex is involved in the ligation step of both BER and repair of DNA single strand breaks. The majority of XRCC1 has previously been demonstrated to exist in a phosphorylated form and cells containing mutant XRCC1, that is unable to be phosphorylated, display a reduced rate of single strand break repair. Here, in an unbiased assay, we demonstrate that the cytoplasmic form of the casein kinase 2 (CK2) protein is the major protein kinase activity involved in phosphorylation of XRCC1 in human cell extracts and that XRCC1 phosphorylation is required for XRCC1-Lig III complex stability. We demonstrate that XRCC1-Lig III complex containing mutant XRCC1, in which CK2 phosphorylation sites have been mutated, is unstable. We also find that a knockdown of CK2 by siRNA results in both reduced XRCC1 phosphorylation and stability, which also leads to a reduced amount of Lig III and accumulation of DNA strand breaks. We therefore propose that CK2 plays an important role in DNA repair by contributing to the stability of XRCC1-Lig III complex.